Copernicus's Heliograph at Olsztyn: The 500th Anniversary of a Scientific Milestone. Issue 11 (12th October 2018) - Graßhoff, Gerd; Fischer, Gordon
Abstract: Exactly 500 years ago, Nicolaus Copernicus drew a lattice of lines on a panel above the doorway to his rooms at Olsztyn Castle, then in the Bishopric of Warmia. Although its design has long been regarded as some kind of reflecting vertical sundial, the exact astronomical designation of the lines and related measuring techniques remained unknown. Surprisingly, Copernicus did not refer to his new observational methods in his principal work, De Revolutionibus . A data analysis of a 3D model of the panel has, at last, solved the mystery: Copernicus created a new type of measuring device—a heliograph with a nonlocal reference meridian—to precisely measure ecliptic longitudes of the Sun around the time of the equinoxes. The data, 3D model, and modeling results of our analysis are open access and available in the form of digital (Jupyter) notebooks. Abstract : Five hundred years ago, Copernicus designed a new type of astronomical measuring instrument, based on the principles of reflecting and inclining vertical sundials. The instrument's lattice of lines drawn above the doorway to Copernicus's rooms at Olsztyn Castle in modern‐day Poland was constructed geometrically and not plotted empirically. This panel has been digitally recorded and computationally modelled, the data of which are now freely accessible in the public domain. Thanks to the reconstruction, Copernicus can, for the very first time, be presented as an innovative, observational astronomer who invented an entirely new kind of measuring instrument.